Patterns Of HRCT In Patients with Pulmonary Tuberculosis At A Tertiary Care Hospital - Anwar, Sohail; Nawaz, Arsalan; Moinuddin, Imran Ahmed; Kashif , Muhammad; Mumtaz, Asim; Bhatti, Muhammad Ijaz (Journal of Rawalpindi Medical College, 2024)
Abstract: Background: With the advancement in biomedical engineering and imaging technology, HRCT scan has emerged as more effective tool than standard1computed tomography scan & traditional chest radiography in detecting pulmonary pathologies including pulmonary tuberculosis. Objective: To determine different patterns of HRCT in patients with pulmonary tuberculosis. Study Design: Retrospective observational study. Setting: Department of Pulmonology & Internal Medicine, University of Lahore Teaching Hospital, Lahore. Methodology: Total of 76 patients were included in the study based on inclusion & exclusion criteria, selected by non-probability consecutive sampling. Demographic information, signs & symptoms and results from high-resolution tomography scans were noted. Data analysis was performed on SPSS 23 & reported by descriptive statistics. Results: Total 76 patients were included. The mean age was 46.18+20.27 years ranging from 8 to 86 years. There were 43(56.6%) males and 33(43.4%) females. 36 (47.37%) patients were up to 45 years of age and 40 (52.63%) patients were above 45 years. Signs and symptoms of pulmonary TB were cough 60 (78.9%), sputum 21(27.6%), fever 43(55.3%), night sweats 23(30.3%) & weight loss 36(47.4%). Most common HRCT pattern observed was ill defined nodules (77.6% cases) while atelactasis was the least common HRCT pattern observed (22.4% cases). There was no statistically significant difference (P <0.05) observed between different patterns of HRCT and positive sputum smear. Conclusion: Our study concluded that a HRCT scan is helpful in the identification of the disease and its accompanying spectrum in patients with pulmonary tuberculosis with nodules being the most prevalent HRCT pattern. Key Words: Tuberculosis (TB), High resolution computerized tomography (HRCT)